Izvršitev sklepa o civilni delitvi solastne nepremičnine - Javh, Ana (Podjetje in delo, 2016)
According to the law in force, the judicial procedures for the voluntary and the enforced execution of a decision on civil division are insufficiently and inconsistently regulated, and the legal position of the participants in these procedures are inappropriately legally protected. Judicial practice in this area is disputable and not uniform. All of the above results in ineffective and inefficient procedures. The article highlights the disputable issues of the valid legal regulation and a critical analysis of related judicial practice, and furthermore proposes de lege ferenda solutions to these disputable issues, taking into account, inter alia, the Austrian legal regulation of the issue in question.
Keywords: delitev; izvršilni postopek; nepravdni postopek; nepremičnine; sodna praksa; solastnina